2013
DOI: 10.3346/jkms.2013.28.6.814
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Diabetic Retinopathy and Nephropathy Screening in Korea: The Third and Fourth Korea National Health and Nutrition Examination Survey (KNHANES III and IV)

Abstract: This cross-sectional study was done to identify and determine the socio-demographic and health-related factors associated with diabetic retinopathy and nephropathy screening in Korea. Participants included 2,660 adults, aged 40 or older, with diabetes. Of the 2,660 adults, 998 (37%) and 1,226 (46.1%) had received a diabetic retinopathy and a nephropathy screening within one year, respectively. Regarding retinopathy, subjects older than 65, living in urban areas, with high educational levels, and with self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 23 publications
3
19
0
2
Order By: Relevance
“…Given the situation that certain Japanese diabetic patients with normoalbuminuria and normal renal function showed typical histological patterns of DN, the discovery of a specific and reliable diagnostic and prognostic biomarker, other than albuminuria, is urgently needed and would be indispensable. Rim et al [22] performed a cross-sectional study to identify and determine the sociodemographic and health-related factors associated with diabetic retinopathy and DN screening in Korea. The relatively low screening rates in Korea compared to the Western countries are likely to be due to the difference in the health system, economic situations and national demographics [22].…”
Section: New Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the situation that certain Japanese diabetic patients with normoalbuminuria and normal renal function showed typical histological patterns of DN, the discovery of a specific and reliable diagnostic and prognostic biomarker, other than albuminuria, is urgently needed and would be indispensable. Rim et al [22] performed a cross-sectional study to identify and determine the sociodemographic and health-related factors associated with diabetic retinopathy and DN screening in Korea. The relatively low screening rates in Korea compared to the Western countries are likely to be due to the difference in the health system, economic situations and national demographics [22].…”
Section: New Biomarkersmentioning
confidence: 99%
“…Rim et al [22] performed a cross-sectional study to identify and determine the sociodemographic and health-related factors associated with diabetic retinopathy and DN screening in Korea. The relatively low screening rates in Korea compared to the Western countries are likely to be due to the difference in the health system, economic situations and national demographics [22]. Chong et al [23] reported the role of renal biopsy in diabetic patients with renal involvement.…”
Section: New Biomarkersmentioning
confidence: 99%
“…Prior reports estimated the overall prevalence of long-term complications in Sudanese adults, with a median duration of diabetes of 9 years, as 67%. Among these the prevalence of retinopathy, neuropathy, cardiovascular disease, nephropathy, peripheral vascular disease, and cerebrovascular accidents were 43%, 37%, 28%, 22%, 10% and 5.5%, respectively (Rim et al 2013). In this study the results for treatment regimen taken showed that 23 (41.1%), of participants were taking oral hypoglycemic agents, which is different from Shigidi research conducted in Khartoum State, Sudan; which showed that 57.9% were on oral hypoglycemic agents (Ahmed & Abdelrhan 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai cara dilakukan untuk mencegah kebutaan akibat retinopati diabetika, di antaranya pencegahan menggunakan metode penapisan yang adekuat, pengobatan retinopati diabetika dengan terapi laser pada keadaan dini, dan metode diagnostik lain dengan bantuan alat seperti angiorafi fundus floresin. 3,4 Seluruh metode untuk penanganan retinopati diabetika tersebut juga membutuhkan akses visualisasi yang baik terhadap keadaan fundus sehingga pupil yang cukup lebar memberikan ruang yang cukup untuk aksesibilitas visualisasi fundus tersebut. Selama ini keadaan tersebut dimungkinkan dengan cara melebarkan pupil menggunakan obat-obatan midriatikum.…”
Section: Pendahuluanunclassified
“…Namun, dikarenakan pada keadaan retinopati diabetika sering ditemukan keadaan neuropati autonomik diabetika, maka pupil penderita diabetes melitus sering sulit lebar. 4,5 Oleh karena itu, konsentrasi obat midriatikum yang diberikan harus lebih tinggi dibanding dengan orang tanpa diabetes untuk mencapai efek midriatikum yang sama. Di samping itu, dikarenakan epitel kornea itu mempunyai efek sawar terhadap seluruh obat yang diteteskan maka konsentrasi obat yang mencapai struktur di dalam bola mata akan berkurang.…”
Section: Pendahuluanunclassified